Peningkatan Kompetesi Speaking Narrative dengan Menggunakan Model Pembelajaran Role Playing bagi Peserta Didik Kelas X 1 SMK Negeri 1 Toroh Kabupaten Grobogan pada Semester 2 tahun Pembelajara 2014/2015 - Lestari, Puspa (widiyanto, 2016)
The outline of the research issue are how is the process of learning and improving speaking narative using the Role Playing model for students of class X-1 1st Toroh Senior Hight School 2nd Semester 2014/2015. The research is crried out though 2 cycles. Each cycle has two meetings. The subject of the research is the students of 1st Toroh Senior High School X-1 2nd semester school year 2014/2015. The average cycle I 80,26 with 66% reached the KKM and cycle OO average 85,39 with 89% reach the KKM, followed by a good atitude.